A STUDY ON ADAPTATION OF SKILL SETS IN THE AGE OF ARTIFICIAL INTELLIGENCE; PORTRAIT OF THE MODERN KNOWLEDGE WORKER (CAHIERS MAGELLANES-NS, 2024)
The advent of artificial intelligence (AI) has catalyzed significant transformations across various sectors, demanding a reevaluation of the skill sets required for modern knowledge workers. The article explores the dynamic landscape of AI-driven workplaces and the evolving competencies necessary to thrive in this environment. It highlights the shift from traditional knowledge-based skills to more adaptive, cognitive, and interpersonal abilities. As AI increasingly automates routine tasks, the emphasis for workers has shifted towards higher-order thinking, creativity, emotional intelligence, and lifelong learning. Artificial intelligence is redefining the boundaries of human capabilities and transforming job roles across various industries. The modern knowledge worker must navigate a complex interplay of technological advancements.. The article investigates how AI is reshaping the skill sets required for knowledge workers and provides insights into the competencies that will be essential in the near future. AI's integration into the workplace has led to the automation of many routine and repetitive tasks, necessitating a shift in the focus of human labor. Job roles are evolving, with a growing demand for skills that complement rather than compete with AI. This transition underscores the need for workers to develop a hybrid set of skills that include both technical proficiency and uniquely human attributes.